1988
DOI: 10.1093/protein/2.4.301
|View full text |Cite
|
Sign up to set email alerts
|

A new recombinant procoagulant protein derived from the cDNA encoding human factor VIII

Abstract: We have constructed new B domain deletion derivatives of human factor VIII (FVIII) by manipulating the cDNA using recombinant DNA techniques. One of these new derivatives, FVIII delta II, in which amino acids 771(pro)-1666(asp) have been deleted, no longer contains the protease cleavage site at amino acid position 1648(arg)-1649(glu) known to be involved in the initial step of FVIII processing. We have expressed this molecule in both baby hamster kidney (BHK) 21 cells using the vaccinia virus (VV) expression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 0 publications
0
35
0
1
Order By: Relevance
“…Previous studies on the requirements for functional activity of FVIII demonstrated that cleavage after Arg residues 372 and 1689 both were required for activation of factor VIII and that the B domain was not required for functional activity (13,(22)(23)(24). Deletion of residues 741-1689 yielded a functional molecule (90͞73) that displayed WT thrombin cleavage and activation, resulting in a heterotrimer similar to WT FVIIIa that was susceptible to rapid dissociation of the A2 subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the requirements for functional activity of FVIII demonstrated that cleavage after Arg residues 372 and 1689 both were required for activation of factor VIII and that the B domain was not required for functional activity (13,(22)(23)(24). Deletion of residues 741-1689 yielded a functional molecule (90͞73) that displayed WT thrombin cleavage and activation, resulting in a heterotrimer similar to WT FVIIIa that was susceptible to rapid dissociation of the A2 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage after residue Arg-740 releases the heavily glycosylated B domain. Previous studies demonstrated that the B domain of FVIII is dispensable for FVIII cofactor activity (22)(23)(24). Genetically engineered FVIII molecules that have varying degrees of B domain deletion yield functional FVIII molecules that are more efficiently expressed in mammalian cells (22,23,25,26).…”
mentioning
confidence: 99%
“…Other authors have reported the construction and expression of recombinant factor VIII lacking most or all of the B domain (Eaton et al, 1986;Toole et al, 1986;Sarver et al, 1987;Lagner et al, 1988;Meulien et al, 1988;Bihoreau et al, 1991;Pittman et al, 1993). The products of the single cDNA gene constructs described either contained the light and heavy chains and, in addition, the single peptide chain representing the nonprocessed primary translation product as the main species or the latter peptide chain as most dominating component.…”
mentioning
confidence: 99%
“…Considering these structural requirements and the necessity for a therapeutic purpose to dispose of a greatly secreted protein, a second-generation antihaemophilia A factor, FVIIIAll, has been constructed [9]. This recombinant protein, lacking a large portion of the B domain (Pro771 -Asp1666) and the amino-terminal part of the light chain, contains the different thrombin-cleavage sites present in the heavy and light chains of the pd-FVIII.…”
mentioning
confidence: 99%